Analisis Gaya Kepemimpinan Terhadap Kualitas Pelayanan di Desa Sungai Ambangah Kecamatan Sungai Raya Kabupaten Kubu Raya - Lorensius, Lorensius; Firayanti, Yuni; Saputra, Edy Suchmawan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
In an organization or other institution, of course there is a leader as the driving force so that an organization or company can run effectively as expected in general. Leadership style is a method or strategy applied by a leader in directing or coordinating his subordinates in order to achieve the expected goals for the common good by not only relying solely on his own abilities in running the leadership of the organization he leads, but there must be cooperation. who is good with his subordinates so that there are no misunderstandings towards those he leads. This research aims to determine the leadership style applied by the Head of Sungai Ambangah Village, Sungai Raya District, Kubu Raya Regency. In preparing this thesis, the author used a qualitative approach research method. This type of research uses direct field research (field research). The data collection technique uses observation, interviews and documentation. The data analysis used descriptive qualitative, while to show the validity of the data the triangulation method was used. This triangulation method is divided into three, namely; Method Triangulation, Data Source Triangulation, and Time Triangulation.The results of this research show that the leadership style applied in Sungai Ambangah Village is in a democratic and charismatic leadership style situation. The results of this research were obtained based on the characteristics shown by the Head of Sungai Ambangah Village as the leader.